MATERIAL SEMIOTICS PERSPECTIVE ON CHU LACQUERWARE: ANALYSIS OF IMPLICIT SYMBOLIC LANGUAGE IN FUTURE DESIGN SCENARIOS - Lyu , Wenhui; Hapiz, Hana; Radzuan, Ainul Wahida (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
The expression form of symbols carries the significance and profound connotations of culture. As the core material carrier of Chu culture, Chu lacquerware has formed a rich symbol system and aesthetic craftsmanship in the unique cultural ecosystem of the Chu region. This article takes typical Chu lacquerware as the research object. From the perspective of material semiotics and in combination with the theory of cultural ecology, it first sorts out the origin, definition and classification of the body craftsmanship of Chu lacquerware, compares its differences and characteristics with those of lacquerware in the Ba-Shu and Central Plains regions, and reveals the craftsmanship advantages and regional cultural attributes of Chu lacquerware during the Warring States Period. Secondly, deeply deconstruct the symbolic language system of Chu lacquerware, including the realistic, imaginative and "image-based" expressions at the form level, the features, design logic and classification at the pattern level, as well as the symbolic meanings of the colours mainly in red and black. Finally, on this basis, the application of Chu lacquerware cultural language in future design fields such as urban trash cans, furniture design, clothing design, and cultural and creative design is mainly discussed. The research aims to explain the semantics, categories and media of Chu's symbolic language, reveal the design concepts and aesthetic roots of Chu culture's symbolic forms, and provide innovative ideas and practical paths from the perspective of Chu culture for contemporary and future design.